STUDI KORELASI ANTARA NILAI UJIAN NASIONAL MATEMATIKA TINGKAT SMA/SMK TERHADAP NILAI MATEMATIKA TERAPAN TARUNA/I AKADEMI MARITIM NUSANTARA (AMN) CILACAP - Luthfiana Tarida (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2017)
One of the factors which affect the quality of graduates of a university was the quality of input. The quality of the input related to the requirements for passing entrance exams for prospective students. The value of National Examination contributed in that case. Some results from research said there was an effect between the value of the National Examination with other variables. Mathematics material obtained from the level of education of Elementary School until Higher Education. Mathematics was a field of study that provides many benefits to other disciplines. Therefore the researchers wanted to know the effect between Mathematics National Examination from Senior High School and the value of Applied Mathematics’s cadets from AMN Cilacap. This research was a quantitative research with population of all cadets in Nautical Science (2015). The sampling technique was done by random sampling so as to produce sample cadets in the Nautical Science of class A. The independent variable in this research was Mathematics National Examination. The dependent variable was value of Applied Mathematics. Data was analyzed using a linear correlation test with SPSS software. The result showed that the result obtained with significance value (Sig.) which gave conclusion no effect between Mathematics National Examination from Senior High School and the value of Applied Mathematics’s cadets in Nautical Science of AMN Cilacap.